Security and resilience in intelligent data-centric systems and communication networks - Ficco, Massimo; Palmieri, Francesco (Academic Press, an imprint of Elsevier, 2018)
This book presents research in theoretical and practical resilience and security aspects of intelligent data-centric critical systems and networks. It also analyzes concepts and technologies that are successfully used in the implementation of intelligent data-centric critical systems and communication networks, touching on future developments